A Note on the Asymptotic Behavior of Parabolic Monge-Ampère Equations on Riemannian Manifolds - Qiang Ru (Journal of Applied Mathematics)
We study the asymptotic behavior of the parabolic Monge-Ampère equation in , in , where is a compact complete Riemannian manifold, λ is a positive real parameter, and is a smooth function. We show a meaningful asymptotic result which is more general than those in Huisken, 1997.